Okoliczności, przy których zaistnieniu możliwe jest sporządzenie testamentu ustnego według polskiego prawa spadkowego - Kuźmicka-Sulikowska, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
This article attempts to specify in what circumstances, in the light of Polish inheritance law, it is possible to make an oral testament. Th e legislator limits the possibility of using this form of will to three cases, namely to the situation when there is a fear of imminent death of the testator, or if due to special circumstances the preparation of the ordinary form of the testament is impossible or very difficult. The article contains an interpretation of the provision stipulating the possibility of making an oral testament only when either of these circumstances occurred. For this purpose, among other things, it was considered whether accepting that there is concern about the imminent death of the testator must be justified by objective or subjective factors, or perhaps both of them at once. It was also considered how to treat cases when the testament is made by a person who wants to commit suicide or someone who, as a result of a medical diagnosis, is convinced that he will soon die, and this diagnosis turns out to be wrong. It was also questioned whether it is reasonable to treat an elderly person’s very old age as a circumstance justifying the fear of imminent death and, consequently, allowing an oral testament to be made. The article also refers to the issue when it can be assumed that due to special circumstances the preparation of the ordinary form of the testament is impossible or very difficult.
Keywords: polskie prawo spadkowe; testament; specjalna forma testamentu; testament ustny